Numerical evaluations on the characteristics of turbulent flow and heat transfer in the Lightnin static mixer. (August 2020) - Meng, Huibo; Han, Mengqi; Yu, Yanfang; Wang, Zongyong; Wu, Jianhua
Highlights: Taking into the effects of Re and A r, a general friction correlation is proposed. The vortices before and after the element transitions have free and forced nature. Two pairs of Dean Vortices occur at the 0.2 l −0.5 l of mixing element. The synergy between secondary flow and temperature field has been investigated. The enhancement degree is evaluated based on thermal and mixing performance. Abstract: Numerical simulations of turbulent flow and heat transfer in the Lightnin and Kenics static mixer are performed using the Fluid Dynamics model ANSYS FLUENT in the range of Re  = 4000-30000 under the uniform wall temperature. The numerically predicted Nusselt number and Darcy friction factor in the KSM has a good agreement with the literature experimental data. The heat transfer performance, flow characteristics, mixing performance and entropy generation characteristics are evaluated with five different aspect ratios of A r  = 1.0, 1.5, 2.0, 3.0, 4.0, respectively. From the leading edge to 0.2 l of each mixing segment, the secondary vortices are dominated by the two pairs of forced vortices. Two pairs of Dean Vortices occur at the 0.2 l -0.5 l derived from the upstream forced vortices and the gradually growing free vortices which dominate the enhancement of heat transfer in the second half of each mixing segment. The Nusselt number Nu increases with the increasing Re and decreasing A r . Compared with Nu in the KSM, the Nu in the LSM with A r  = 1.0 increase by 37%-47% and the Darcy friction factor increase by 81%-82%. With the increasing Re, the values of thermo-hydraulic performance factor η H for A r  = 1.0 and 1.5 firstly decrease and then stabilize above 1.1. Taking into consideration of the coupling effects between Re and A r, a new empirical friction relationship in LSM under the turbulent condition is proposed with the maximum deviation less than 8.55%. The irreversible energy loss in the LSM is no more than 52.88% of that in the KSM and 95% of entropy generation rate is caused by turbulent heat transfer under the constant heat flux. The integral enhancement degree is evaluated by the product of thermal-hydraulic and shear mixing performance which indicates that LSM instead of KSM is an economical and effective choice for comprehensive heat transfer performance.